PENGEMBANGAN MODUL AJAR BIOLOGIBERBASIS PROBLEM SOLVINGTERHADAPKEMAMPUANPEMECAHANMASALAHSISWA - Wiyan Suryani, Wiyan Suryani (UNIVERSITAS HAMZANWADI, 2025)
This study aims to: (1) Develop a biology teaching module based on Problem Solving for problem solving ability in students. (2) To determine the validity of the biology teaching module based on Problem Solving for problem solving ability in students. (3) To determine the effectiveness of the biology teaching module based on Problem Solving for problem solving ability in students. The trial subjects in this study were material experts, biology teachers, design experts, 16 students in small-scale trials, 40 students in limited trials at MA NW Sepit. Problem solving ability is crucial in academic contexts and everyday life, so an appropriate learning strategy is needed. In this study, the teaching module was developed using the 4-D model, with the stages of define, design, and develop. The evaluation results showed that the developed module was very valid with an average feasibility of 92.13% from material expert I, 87.04% from material expert II, and 81.33% from design experts. Student responses to the module also showed a feasibility percentage of 86.42%, indicating that this module is ready to be applied in learning. Testing the effectiveness of the module through pretest and posttest showed a significant increase in students’ problem-solving abilities. The experimental class showed an N-Gain of 0.75, which is categorized as high, compared to the control class with an N-Gain of 0.26 which is categorized as low. This finding confirms that the Problem Solving approach in the teaching module is able to improve students' skills in solving problems. From the results of the study, it can be concluded that the development of a Problem Solving-based teaching module is not only valid and ideal, but also effective in improving students’ problem- solving abilities, which supports the goal of education to produce creative and competent individuals